Characterization on titanium surfaces and its effect on photocatalytic bactericidal activity - Joo, Hyeon-Cheol; Lim, Young-Jun; Kim, Myung-Joo; Kwon, Ho-Beom; Han, Jun-Hyun (ELSEVIER, 2010)
Many studies have been published on the use of TiO2 as a photocatalyst, which decomposes various organic compounds under UV illumination by generating various radicals. The purpose of the present study was to evaluate the photocatalytic bactericidal effects of variously treated titanium surfaces on Escherichia coli K-12. The specimens were fabricated from grade 4 commercially pure titanium, 12mm in diameter and 1mm in thickness. Five different surfaces were prepared (MA: machined surface; AO: anodized at 300 V; NO: NaOH-treated; NW: NaOH- and water-treated; and HT: heat-treated). Surface analysis was performed using scanning electron microscopy, optical interferometer, and thin-film X-ray diffractometry. Photocatalytic activity of each group was confirmed by degradation of methylene blue (MB). The antibacterial activity was assessed by calculating the survival ratio in a drop of a culture of E. coli placed on the surface under UV illumination. Significant photocatalytic activity and bactericidal effects were observed on the titanium surfaces of AO and NW, regardless of the surface roughness (P < 0.01). The group with anatase was the most susceptible to the photocatalytic effect, while the surface without anatase showed the least susceptibility. Based on this in vitro study, the crystallography of the oxide layer on its titanium surfaces is an important factor affecting the photocatalytic bactericidal activity. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: THIN-FILMS; ANATASE; INTEGRATION; ROUGHNESS; COATINGS; RUTILE